2018
DOI: 10.1101/324319
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acetylcholine inhibits platelet activation and regulates hemostasis

Abstract: 22Word Count: 5145 23 Figure Count: 5 figures 24 25 26 42 platelets express members of the acetylcholine signaling pathway including CHRNA2, CHRNA7,43 CHRNB1, and ACHE. Platelets from mice lacking Chrna7 are hyperactive when stimulated by 44 thrombin and resistant to inhibition by acetylcholine. Furthermore, acetylcholinesterase 45 inhibitors prolonged bleeding in wild-type mice. Knockout mice lacking Chrna7 subunits of the 46 acetylcholine receptor display prolonged bleeding as well. 47 52 Abbreviations 53 NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…43 Furthermore, Bennett et al revealed that carbachol, an analog of acetylcholine, inhibits platelet activation through the attenuation of thrombin receptor. 44 In addition, AChEIs have been reported as having an anti-platelet effect in the endothelial cells, which play an essential role in ischemic stroke development. 36 These differences could be due to a different population being studied, seeing as we placed an emphasis on non-hypertensive AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…43 Furthermore, Bennett et al revealed that carbachol, an analog of acetylcholine, inhibits platelet activation through the attenuation of thrombin receptor. 44 In addition, AChEIs have been reported as having an anti-platelet effect in the endothelial cells, which play an essential role in ischemic stroke development. 36 These differences could be due to a different population being studied, seeing as we placed an emphasis on non-hypertensive AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…pulmonary embolisms. Acetylcholine is known to reduce platelet activation via α7 nicotinic acetylcholine receptors (α7nAChR) (8)(9)(10). Accumulating evidence suggests that stimulated platelets generate choline products, which activate the α7nAChR, resulting in a positive anti-inflammatory and anti-thrombotic impact.…”
Section: Introductionmentioning
confidence: 99%